The effectiveness of the material experience program national examination in vocational high schools - Nurul Chairani; Siti Mariah (Jurnal Taman Vokasi, 2018)
This study aims to determine the effectiveness of the deepening program of national exam materialsof vocational students in Bantul District. This research is evaluation research with CPRP (Context, Input, Process,and Product) evaluation model from Stufflebeam using quantitative approach supported by qualitative. Data werecollected using questionnaires, interviews, observations, and documentation. The results of the research are, first,the context is very useful, shown by organizational program organizers have been structured, and the program isvery relevant to the needs of students; Second, the input is quite effective, the readiness of the students to followthe program and management has been well managed, the program plan is very effective, the program strategy isquite effective, and the learning media is very useful; Third, the process is quite effective indicated by the level ofstudent participation in the implementation of the morning is lower than the daytime. Learning process accordingto program planning; Fourth, the product aspect is very effective with the benefits of the program.